Isolation And Characterization Of Phosphate Solubilizing Fungi From Fruit And Vegetable Peel Waste Compost Fertilizer - Sri Wulan Desi Sasmita; Walida Hilwa; Dalimunthe Badrul Ainy; Harahap FS (International Journal of Science and Environment (IJSE), 2023)
Phosphate solubilizing fungi are fungi that can convert phosphate in soil from compound form (almost insoluble) into ionic form (easily soluble) so that it can be utilized by plants. The purpose of this study was to determine the isolation and characteristics of phosphate solubilizing fungi isolates found in fruit and vegetable peel waste compost. This research was conducted in January 2023 until completion in the Laboratory of the Faculty of Science and Technology, Labuhanbatu University. This research was carried out by isolating fungi from municipal waste compost, characterizing morphology and the ability to dissolve phosphate and molecular identification. Furthermore, the data were analyzed descriptively based on the research results obtained. There were 4 isolates of phosphate solubilizing fungi that were able to form clear zones on Pikovskaya media with different morphological characteristics and ability to dissolve phosphate. The largest clear zone diameter was shown in isolate A3 of 3 cm which is Aspergillus niger fungus.